Microbial dynamics of acute pancreatitis: integrating culture, sequencing, and bile impact on bacterial populations and gaseous metabolites - Chmielarczyk, Agnieszka; Golińska, Edyta; Tomusiak-Plebanek, Anna; Żeber-Lubecka, Natalia; Kulecka, Maria; Szczepanik, Antoni; Jedlińska, Katarzyna; Mech, Krzysztof; Szaciłowski, Konrad; Kuziak, Agata; Pietrzyk, Agata; Strus, Magdalena (Frontiers in Microbiology, 2025)
BackgroundOur study examined the composition of the intestinal microflora in a hospitalized patient with AP symptoms treated several months earlier for diverticulitis. The therapeutic intervention necessitated Hartmann's procedure, culminating in colostomy creation.AimsEmploying a thorough microbiological analysis we attempted to demonstrate whether the microflora isolated from the peripancreatic fluid exhibited a stronger correlation with the contents of the stoma or with the rectal swab. Additionally, we sought to determine the association between later onset of AP and diverticulitis.MethodsFollowing clinical materials from the patient in the initial phase of AP were collected: rectal swab, colostomy bag contents (in the publication referred to as stoma content/stool) and peripancreatic fluid. Microbiological analysis was performed, including classic culture methodology, NGS techniques, and genotyping methodologies. Furthermore, the effect of bile on the shift in the population of selected bacterial species was examined.ResultsThe NGS technique confirmed greater consistency in bacteria percentage (phyla/family) between stoma content and peripancreatic fluid. In both samples, a clear dominance of the Proteobacteria phyla (over 75%) and the Enterobacteriaceae family was demonstrated. Moreover, NGS verified the presence of the Fusobacteriota phylum and Fusobacteriaceae family only in rectal swabs, which may indicate a link between this type of bacteria and the etiology of diverticulitis. We observed that Escherichia coli 33 isolated from stool exhibited active gaseous metabolite production (mainly hydrogen).ConclusionsThe abundant production of hydrogen may substantially impact enzymatic processes, inducing specific alterations in disulfide bonds and trypsin inactivation. Our investigation alludes to the conceivable active involvement of bile in effecting qualitative and quantitative modifications in the peripancreatic microbiota composition, establishing a correlation between released bile and bacterial generation of gaseous metabolites.